Innovative Information and Knowledge Sharing Platform for Business Sector: Focus on Intranet-based Social Network Service - Jimin Kim; Younghoon Chang; Sangman Lee; Myeong-cheol Park (International Telecommunications Society (ITS), 2012)
Recently, ICT ecosystems are changing rapidly due to the increasing number of innovative products and services in these ecosystems. Among them, SNS is one of the most important elements that make up the ICT ecosystem. With the phenomenal boom of personal SNS, information and knowledge sharing within an organization through enterprise SNS is increasing exponentially. Many companies are adopting and using intranet-based SNS for communicating and sharing information within the firm. However, there have not been many studies exploring the impact of group intentions on the SNS service within a firm. In this study, we investigate user intentions as they relate to intranet-based SNS as better information and knowledge sharing communication tools which improve existing internal communication methods due to their system-wide implementation of a top-down approach and mandatory participation. To do this, this study developed a research model for an intranet-based SNS service based on social exchange theory, social learning theory, motivation theory and We-Intention theory. The results indicated that employees desire to use SNS service when they perceive a reciprocal benefit for themselves and other employees. Usability only affects desire and sociability affects what is termed here as We-Intention. However, sociability's result is opposite in that sociability directly affects We-Intention. Considering that communication and interaction between group members are recently increasingly important, this research results are academically significant because they suggest a meaningful implication to vitalizing information and knowledge sharing in organizations through the use of intranet-based SNS.
Keywords: 650; We-Intention; Intranet-based SNS; Enterprise SNS; Enterprise 2.0; Social Learning Theory; Socio-technical System; Social Exchange Theory